Security Regulations in the Constitution of the Republic of Poland - Jakubiak, Ewa; Chrzanowski, Mariusz (PRAWO i WIĘŹ, 2025)
The essence of understanding the concept of security is constantly expanding with the development of civilization with unknown threats and innovative ways of eliminating them. The aim of this paper is to present the security pillars in the Polish constitution, which include principles, institutions and legal mechanisms that are aimed at ensuring stability, protecting the sovereignty of the state and the rights and freedoms of citizens. The Polish Constitution of 1997 contains many key provisions that serve the function of protecting national and state security, both internally and externally. The idea of national security is as old as the state. The people who created the first community and state formation had from the very beginning an idea of their means of subsistence and protection against external and internal threats. In order to achieve and maintain the desired level of security, Poland, like other countries, uses instruments in the form of legal and material regulations. The security of the state and its citizens is an important pillar of public order in the state. The theoretical and legal method was used in this paper.